Improved Encryption Algorithms Based on Addition Table of Galois Fie - Hasan Kadhim Ali Alsuwaiedi; Supervised By Prof. Dr. Abdul Monem S. Rahma (2025)
Dissertation Submitted to the Informatics Institute for Postgraduate Studies At the Iraqi Commission for Computers and Informatics in a Partial Fulfillment of the Requirement for the Degree of Doctorate of Philosophy in Computer Science.